Ionic liquids as modulators of fragrance release in consumer goods. (21st October 2016) - Ferrero Vallana, Federico M.; Girling, Ricardo P.; Nimal Gunaratne, H. Q.; Holland, Lynette A. M.; Mcnamee, Pauline M.; Seddon, Kenneth R.; Stonehouse, Jonathan R.; Todini, Oreste
Abstract : The vapour–liquid equilibria of organic molecules dissolved in ionic liquids revealed positive deviation from Raoult's law, especially with added water. Abstract : When organic esters or alcohols were dissolved in each of three novel ionic liquids (which have no effective vapour pressure), the vapour–liquid equilibria (as measured by infrared spectroscopy of the gas phase) revealed significant positive deviation from Raoult's law for a wide range of perfume raw materials. The addition of water amplified the repulsive effect of the ionic liquid matrix, and this was exemplified by a series of ternary phase diagrams.